Impacts of improved seed maize technology adoption on productivity and technical efficiency in Northern Ghana - Emmanuel Dokyi; Benjamin Tetteh Anang; Victor Owusu (Open Economics, 2021)
Improved seed is one of the crucial ingredients for promoting agricultural productivity, farmers' livelihood, and global food security. The present study uses an endogenous treatment regression model (ETRM) to evaluate the impacts of improved seed maize technology (ISMT) adoption on technical efficiency and productivity using data from maize farmers in northern Ghana. The findings show that ISMT adoption impacts positively on technical efficiency. Adoption of ISMT enhanced technical efficiency by 16.1% and increased maize productivity by 33.8%. The study recommends dissemination of improved maize seeds to farmers and other interventions such as provision of fertilizer to enhance farmers' technical efficiency and productivity.
Keywords: C21; D24; Q12; 330; adoption; endogenous treatment-regression model; stochastic frontier analysis; technical efficiency; Tolon District